1987
DOI: 10.1002/pd.1970070407
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of trisomy 20 mosaicism indicating an extra embryonic origin

Abstract: An additional case of amniotic fluid trisomy 20 mosaicism is presented. After careful counselling, the pregnancy continued and a phenotypically normal female was delivered. This case of amniocyte mosaicism establishes the source of aneuploid cell line as amnion. Since an extra-embryonic origin of the mosaicism has been confirmed, this should be carefully considered as a real possibility in counselling such families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 9 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…The origin of cells with trisomy 20 occurring in amniotic fluid was in fact amniotic (Baldinger et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The origin of cells with trisomy 20 occurring in amniotic fluid was in fact amniotic (Baldinger et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of cases have been identified on amniocentesis rather than CVS, it has been suggested that the benign nature results from the trisomic cell line being restricted to the placental tissues in cases with no foetal abnormality. 9 A trisomic cell line has been confirmed postnatally, however, in biopsy tissue and other specimens from seven physically and developmentally normal children previously investigated. 1,11 Trisomic cells have been detected frequently in fibroblast cultures following skin biopsy or from foreskin tissue and also from the gastrointestinal tract, muscle, fascia, kidney and lungs with no clear association with abnormality.…”
Section: Discussionmentioning
confidence: 84%
“…Early cases frequently led to pregnancy termination; however, only a small proportion of fetuses (15%) were noted to have significant anomalies (for reviews, see Hsu et al 1987 and Hsu et al 199 1). Several cases detected following amniocentesis showed only normal karyotypes in various tissues examined from the liveborn infant (Abuelo et al 1986, Baldinger et al 1987, Tolmie et al 1987, Hsu et a]. 1987, Hsu et al 1991.…”
mentioning
confidence: 99%
“…Risk figures for use in genetic counseling are difficult to present due to follow-up data on only a minimal number of cases of mosaic trisomy 20. It had been suggested that there was a positive correlation between frequency of trisomy 20 cells and major phenotypic abnormalities (Djalali et al 1985, Hsu et al 1987), yet these data are not conclusive, and certainly cases have been reported with greater than 50% trisomy 20 cells detected in amniocytes that later led to a phenotypically normal fetus (Donnenfeld et al 1987, Baldinger et al 1987.…”
mentioning
confidence: 99%